2000
DOI: 10.1128/jb.182.13.3784-3793.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Investigation of the Catabolic Pathway for Degradation of Abietane Diterpenoids by Pseudomonas abietaniphila BKME-9

Abstract: We have cloned and sequenced the dit gene cluster encoding enzymes of the catabolic pathway for abietane diterpenoid degradation by Pseudomonas abietaniphila BKME-9. The dit gene cluster is located on a 16.7-kb DNA fragment containing 13 complete open reading frames (ORFs) and 1 partial ORF. The genes ditA1A2A3 encode the ␣ and ␤ subunits and the ferredoxin of the dioxygenase which hydroxylates 7-oxodehydroabietic acid to 7-oxo-11,12-dihydroxy-8,13-abietadien acid. The dioxygenase mutant strain BKME-941 (ditA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 45 publications
9
75
0
Order By: Relevance
“…In fact, a pimerane diterpenoid, isopimaric acid, and a chlorinated diterpenoid, 12,14-dichlorodehydroabietic acid, also induced ditQ, despite these two compounds not being growth substrates for BKME-9. However, this is not surprising considering that the same inducers were identified for ditA1 and ditA3, the genes encoding the ␣ subunit and ferredoxin of the ring-hydroxylating dioxygenase, respectively (14). As previ- ously seen with the dioxygenase components, nonditerpenoid compounds did not induce expression of ditQ above the level of the pyruvate control.…”
Section: Fg(f/h)g(p/s)h(m/l)cmentioning
confidence: 89%
See 3 more Smart Citations
“…In fact, a pimerane diterpenoid, isopimaric acid, and a chlorinated diterpenoid, 12,14-dichlorodehydroabietic acid, also induced ditQ, despite these two compounds not being growth substrates for BKME-9. However, this is not surprising considering that the same inducers were identified for ditA1 and ditA3, the genes encoding the ␣ subunit and ferredoxin of the ring-hydroxylating dioxygenase, respectively (14). As previ- ously seen with the dioxygenase components, nonditerpenoid compounds did not induce expression of ditQ above the level of the pyruvate control.…”
Section: Fg(f/h)g(p/s)h(m/l)cmentioning
confidence: 89%
“…Previously, it was reported that wild-type BKME-9 shows no endogenous catechol-2,3-dioxygenase (C23O) activity and that activity served as an adequate reporter for gene induction studies (14). For C23O assays, strain P450KO was grown on mineral medium supplemented with 1 g of sodium pyruvate/liter to an OD 600 between 0.15 and 0.3 and then spiked with a potential inducer, 150 mg of DhA/liter, 150 mg of AbA/liter, 158 mg of 7-oxo-DhA/liter, 150 mg of isopimaric acid/liter, 37 mg of 12,14-dichlorodehydroabietic acid/liter, 15.4 mg of biphenyl/liter, 12.0 mg of naphthalene/liter, or 17.8 mg of phenanthrene/liter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds are synthesized by trees as defense molecules and several bacteria, including Pseudomonas abietaniphila and Burkholderia xenovorans, can use abietane diterpenoids as the sole carbon source (24,25). Twenty-three of the P. aeruginosa dit genes (PA2G 01983 to PA2G 02008) are highly homologous to genes in P. abietaniphila BKME-9 (62-91% sequence identity of their protein products) with conserved synteny (26). Several orthologs are found in the B. xenovorans genome, although synteny with the PA2192 is less conserved.…”
Section: Evolution Of Rgp29 In Strain Pa2192 and Acquisition Of New Mmentioning
confidence: 99%